Cardiac Involvement in COVID-19: A Global Bibliometric and Visualized Analysis - Xu, Si-chi; Zhao, Xin-yue; Xing, Hai-ping; Wu, Wei; Zhang, Shu-yang (Frontiers in Cardiovascular Medicine, 2022)
Objective: Coronavirus disease 2019 (COVID-19), which was caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), had already resulted in widespread epidemics worldwide and millions of people deaths since its outbreak in 2019. COVID-19 had also been demonstrated to affect people’s cardiac function. However, the specific mechanism and influence of this damage were not known yet. The purpose of the present study was to provide a bibliometric analysis of the current studies related to cardiac involvement after SARS-CoV-2 infection. Methods: A bibliometric literature search was performed on the web of science. The number and type of publications, countries, institutional sources, journals, and citation patterns were analyzed. In addition, qualitative and quantitative evaluations were carried out to visualize the scientific achievements in this field by using VOSviewer software. Results: Web of science had recorded 224097 documents on COVID-19 at the time of data collection (May 12, 2022). A total of 2025 documents related to cardiac involvement were recorded at last. The countries with the most published articles were the United States of America (USA) (n =747, 36.9%), Italy (n =324, 16%), and England (n =213, 10.5%). Although the countries and institutions that publish the most articles were mainly from the USA, the top three authors were from Germany, England, and Poland. Frontiers in Cardiovascular Medicine was the journal with the most studies (65 3.2%), followed by ESC HEART FAIL (59 2.9%) and Journal of Clinical Medicine (56 2.8%). We identified 13739 authors, among which Klingel, Karin, and Harky, Amer had the most articles, and Shaobo Shi was co-cited most often. There existed some cooperation between different authors, but the scope was limited. Myocarditis and heart failure (HF) were the main research hotspots of COVID-19 on cardiac dysfunction and may be crucial to the prognosis of patients. Conclusions: This is the first bibliometric analysis of publications related to COVID-19-associated cardiac disorder. This study provides academics and researchers with useful information of the most influential articles on COVID-19 and cardiac dysfunction. Cooperation between countries and institutions must be strengthened on myocarditis and HF during COVID -19 pandemic.